Neoperlops vietnamellus, a rare stonefly from Vietnam (Plecoptera: Perlidae) - Cao, Thi Kim Thu; Bae, Yeon Jae (Zootaxa, 2008)
A rare perlid stonefly, Neoperlops vietnamellus, sp. nov., is described from Vietnam. Descriptions and figures of key characters are provided for the male and female adult, nymph, and egg stages. The male adult of N. vietnamellus can be distinguished from other congeners by its unique distribution of patches of sensilla basiconica posteromesally on the abdominal terga VII–IX, by the absence of sensilla basiconica on the anterior processes of the hemiterga, and by the absence of prominent spines along ventral edge of the hemiterga. The female adult has a slightly protruding subgenital plate on the abdominal sternum VIII as a strongly sclerotized mesal tab. The nymphs can be distinguished by the distinct M-line marking on the head, relatively long cerci, and a lack of dense swimming hairs on cerci. The egg chorion surface is completely smooth, and the anchor features a number of long filaments.